Mapping cropland extent over a complex landscape: An assessment of the best approaches across the Zambezi River basin - Bofana, Jose (2023)
Bofana, Jose. 2023. Mapping cropland extent over a complex landscape: An assessment of the best approaches across the Zambezi River basin. PowerPoint presentation given during the Project Inception Workshop, VIP Grand Hotel, Maputo, Mozambique, April 20, 2023